2015
DOI: 10.1021/acsami.5b04066
|View full text |Cite
|
Sign up to set email alerts
|

Realization of ppb-Scale Toluene-Sensing Abilities with Pt-Functionalized SnO2–ZnO Core–Shell Nanowires

Abstract: In this paper, we report the exceptional toluene-sensing properties of SnO2-ZnO core-shell nanowires (C-S NWs) functionalized with Pt nanoparticles (NPs). A response of 279 was obtained for 100 ppb of toluene, and to the best of our knowledge, this is the highest toluene response to be reported in the literature. The SnO2-ZnO C-S NWs were synthesized via a two-step process: First, a networked core of SnO2 nanowires was prepared via vapor-liquid-solid growth on the patterned electrode layer. Second, the ZnO she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 62 publications
0
49
0
Order By: Relevance
“…Nevertheless, also in this case, the operating temperature with the highest response is 350 • C [26]. Moreover, Kim et al [34] reported exceptional toluene sensing properties of novel SnO 2 /ZnO core-shell nanowires, functionalized with Pt nanoparticles, showing an excellent R air /R analyte intensity response to 100 ppb at 300 • C. Remarkably, as sticks out, the majority of the most promising reported sensor materials achieve the best performances only at high operating temperatures, especially above 250-300 • C [26,34].…”
Section: Introductionmentioning
confidence: 70%
“…Nevertheless, also in this case, the operating temperature with the highest response is 350 • C [26]. Moreover, Kim et al [34] reported exceptional toluene sensing properties of novel SnO 2 /ZnO core-shell nanowires, functionalized with Pt nanoparticles, showing an excellent R air /R analyte intensity response to 100 ppb at 300 • C. Remarkably, as sticks out, the majority of the most promising reported sensor materials achieve the best performances only at high operating temperatures, especially above 250-300 • C [26,34].…”
Section: Introductionmentioning
confidence: 70%
“…Jae-Hun et al ever reported that the CuO-ZnO C-S nanowires sensor showed the highest response to CO and C 6 H 6 at a shell thickness close to Debye length (λ D ) of ZnO [32]; while according to the investigation from Park et al, the critical thickness for the shell in In 2 O 3 -ZnO C-S nanowires sensor was very close to 2λ D of ZnO [33]. The sensing mechanism of these metal oxide C-S structures has been demonstrated with several models such as the potential barrier-controlled carrier transport and the radial modulation effect in the electrondepleted shell [34][35][36][37][38]. For LNWs/PPy C-S nanowires sensors in this work, different correlation between gas response and shell thickness is revealed.…”
Section: Mechanism Discussionmentioning
confidence: 99%
“…Most of the structures reported in the literature are based on ALD of n‐type ZnO thin films deposited onto n‐type metal oxide nanostructures, such as NWs, NRs, and fibers. Core–shell materials have been fabricated by combining ALD with either ES,[48,56b,62,63,67] thermal evaporation,[56f,64,65,68,74,75] vapor–liquid–solid (VLS),[56a,81] or hydrothermal synthesis. An enhancement of sensitivity has been noted when a CS material was used instead of a pure material.…”
Section: Heterostructured Gas Sensorsmentioning
confidence: 99%
“…Metal oxides nanostructures fabricated by ALD were also decorated with metal particles, from wet impregnation processes or attachment of preformed nanoparticles. For instance, γ‐ray radiolysis was used to functionalize SnO 2 ‐core/ALD ZnO‐shell NWs with Pt NPs . The Pt‐CS NWs enabled trace detection of toluene vapor, showing unprecedented sensitivity to 100 ppb.…”
Section: Heterostructured Gas Sensorsmentioning
confidence: 99%